Comment utiliser la Journée internationale des archives pour mieux se faire connaître au sein de son organisme: le cas de la ville de Boucherville - Bréard, Julien (Convergence AAQ, 2024)
Par Julien Bréard, chef de section au Service de gestion des documents et des archives, Ville de Boucherville L’image de l’archiviste dans la société est encore et toujours aussi méconnue. Trop de …
Keywords: Profession; Québec

Missions impossibles ? - René-Bazin, Paule; Prax, Hélène (Gazette des archives, 1978)
The relations between the Archives nationales and the Ministries have been entrusted since 1950 to archivists of the Archives nationales with either a permanent or a parttime mission. Since 1967, these relations are also entrusted to the Cité des Archives contemporaines (Intermediate repository) of Fontainebleau. Archivists in charge of the missions describe the organisation of their work and propose some regulatory and technical improvements.